Production and Characterization of Bio-Briquettes from Coconut Leaves and Cassava Peels - Fitriyano, Gema; Ismiyati, Ismiyati; Purnawan, Irfan; Ramadhan, Raihan Fajar (Universitas Sanata Dharma, 2023)
Bio-briquettes from a mixture of coconut leaves charcoal and cassava peels charcoal have been produced and characterized in this study. The analysis carried out included density, burning rate, water content, ash content, and calorific value. Bio-briquette samples were produced with composition variations between coconut leaves charcoal and cassava peels charcoal with mass percentage ratios of 100:0, 75:25, 50:50, 25:75, 0:100. The mixture used to produce briquettes with a ratio of tapioca flour, water and charcoal as raw materials is 1.5:1.5:2. The results of the study show that the density and calorific value of bio-briquettes increases with the increase in the amount of cassava peel in the briquette content. The optimum bio-briquette product from this research was found in variations of coconut leaves and cassava peels with a ratio of 75:25. Where density is 0.96 g/ml, burning rate is 0.190 g/min, water content is 3%, the ash content is 18.81%, and the calorific value is 3521.47 Cal/g.